Election Night Chris Petersen for City Council - Watkins, Howard::::::::: (1985)
Tom Breen, Robert Torres, Barbara Gaines, Chris Torres, Jerry McMenimen in back, ??, John Taylor and wife in gray suit ?, Warren Kessler in back, Chris Petersen and boy holding balloons